P6.065 Sexual Health in Germany - Using Indicators as an Instrument to Describe, Plan and Evaluate. A Catalogue of Indicators of the German STI Society. (13th July 2013) - Jansen, K; Bremer, V; Rüden, U von; Steffan, E; Nitschke, H
Abstract : Background: Sexual health is an integral part of the personal well-being of human beings, as defined by the WHO. Thus, instruments to measure the respective needs, to design appropriate and effective interventions, and to evaluate their impact and success are of high importance. These tools should be adopted on a local, regional and national level. There have been no such instruments available to specify the situation of sexual health in Germany to date. The "Sexual Health" section of the German STI Society has now adopted a set of indicators in order to depict the sexual health status of people in Germany, as well as to plan and evaluate activities for the improvement of sexual health as a whole. Methods: Basis for defining indicators consisted of draught submittals of WHO and EU. All indicators described were considered as to their explanatory power and applicability for the specific German situation in terms of political structures, medical care, and epidemiology, and were partly adopted, revised or complemented by new indicators. Every indicator was operationalised in terms of appropriate variables, type of documentation, administration level, data source, availability, and assessed by its specific importance. Results: 39 indicators on policy and social determinants, 28 on access (availability, information, demand, and quality), 24 on the use of services, and 33 outcome/impact indicators were defined. To allow for flexibility, these categories were grouped by the following subdivisions: general, family planning, maternal and prenatal health, STI/RTI/reproductive morbidities, promotion of sexual health, adolescent sexual education and health, and sexual violence. Conclusion: A logical, convincingly conclusive and yet manageable list of indicators for Germany has been compiled. The selected indicators display the German situation and are at the same time highly comparable internationally. Potential users of the document are health experts, policy developers, researchers and other health care professionals.